Customer Value Determination and its Implications in Customer Loyalty Hotels - Fitrizal, Fitrizal; Limakrisna, Nandan (International Review of Management and Marketing, 2019)
The low customer loyalty to Four-Star Hotels in West Sumatera province was allegedly caused by customer relationship management, service quality and customer value are still low. The purpose of this research was to determine and analyze the effect of customer relationship management and service quality partially or jointly towards customer value. To determine and analyze the effect of customer relationship management, service quality and customer value partially or jointly on customer loyalty. The population of the study are 205 customers Four Star Hotels in West Sumatra province. The method used in this research is a descriptive survey method and explanatory survey with a sample size using rule 1: 5 of 205 respondents, as well as data analysis method used is SEM (Structural Equation Modeling) with Lisrel 8.51 application program. Based on the research results, obtained following research finding that customer relationship management, service quality and customer value proven to have positive and significant impact on customer loyalty with a contribution of 84% while the remaining 16% are influenced by other factors. Based on partial view customers value the most dominant influence on customer loyalty. Keywords: Customer Relationship Management, Service Quality, Customer value, Customer Loyalty. JEL Classifications: M21, M31, Z33 DOI: https://doi.org/10.32479/irmm.7612